Satisfaction with the life of Polish women experiencing domestic violence - Pawłowska-Muc, Agnieszka Konstancja; Pilewska-Kozak, Anna Bogusława; Stadnicka, Grażyna; Kęsik, Jan Jakub; Dobrowolska, Beata (Frontiers in Public Health, 2023)
Introduction Domestic violence against a woman, inflicted by her husband/partner, disrupts the socially recognized model of partnership and family life and endangers the health and life of the victim. The aim of the study was to assess the level of satisfaction with the life of Polish women experiencing domestic violence and compare it to results of women not experiencing domestic violence. Methods A cross-sectional study was conducted on a convenience sample of 610 Polish women divided in two groups: victims of domestic violence (Group 1, n = 305) and women not experiencing domestic violence (Group 2, n = 305). Results and Conclusions Most Polish women experiencing domestic violence are characterized by low life satisfaction. The mean value of life satisfaction in Group 1 was 13.78, SD = 4.88, significantly lower when compared to Group 2 (M = 21.04, SD = 5.61). Their satisfaction with life is related, among other things, to the form of violence inflicted upon them by their husband/partner. Abused women with low life satisfaction are most often victims of psychological violence. The most common cause is the perpetrator's addiction to alcohol and/or drugs. Assessment of their life satisfaction is unrelated to help-seeking and to the occurrence of violence in their family home in the past.